Prediksi Pesediaan Stock Pulsa Menggunakan Fuzzy Linear Regresion - Misdiyanto, Misdiyanto (STIKOM Tunas Bangsa Pematangsiantar, 2019)
Electronic phone credit (pulsa) sales at this time showed an outstanding increase, because of the needs of phone credit usage every day by the society that has now became a need. Phone credit business will never stop because human always communicate with one another. To ensure the availability of the product in the phone credit server, the phone credit server manager routinely, in a particular period, inventorize the purchase of phone credit products. From the exploration above, the market conditions in a business are always changing, In a business. Process prediction is important for every business person in decision-making. Then, there is a need to build a prediction system that could predict phone credit transactions in the next period. Results or output of this system is predictive value of transactions in the next period with average error value of 4% using β1=0,5 and β2=0,2. Therefore, it can be used as a reference for the management in the decision-making.